Closure to Experimental and CFD Analysis of Circular Labyrinth Weirs by Omer Bilhan, M. Cihan Aydin, M. Emin Emiroglu, and Carol J. Miller - Bilhan, Omer; Aydin, M. Cihan; Emiroglu, M. Emin; Miller, Carol J. (Asce-Amer Soc Civil Engineers, 2019)
[Abstract Not Available]